1985
DOI: 10.1002/j.1460-2075.1985.tb03807.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promoter phorbol-12-myristate-13-acetate induces poly(ADP)-ribosylation in fibroblasts.

Abstract: The tumor promoter phorbol-12-myristate-13-acetate (PMA) causes an increase in poly(ADP)-ribosylation in mouse and human fibroblasts via the intermediate formation of active oxygen. In contrast to poly(ADP)-ribosylation induced by the methylating agent N-methyl-N'-nitro-N-nitrosoguanidine, de novo RNA and protein synthesis are required and the accumulation of the polymer occurs in the absence of detectable DNA strand breakage. Our results suggest a mechanism for PMA-induced modulation of chromatin structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…PARP-1 is predominantly nuclear whereas PARG is preferentially cytoplasmic, although a significant proportion is found in the nucleus (Winstall et al, 1999;Ohashi et al, 2003;Bonicalzi et al, 2003). DNA-damage-induced poly(ADP-ribose) is detected within minutes, peaks by 30 minutes and returns to basal levels 15-60 minutes later (Singh et al, 1985;Tartier et al, 2003). Similar kinetics of synthesis/degradation are also observed during transcription of the hsp70 locus in Drosophila (Tulin and Spradling, 2003).…”
Section: Poly(adp-ribose) Glycohydrolase and Chromatin Recondensationmentioning
confidence: 76%
“…PARP-1 is predominantly nuclear whereas PARG is preferentially cytoplasmic, although a significant proportion is found in the nucleus (Winstall et al, 1999;Ohashi et al, 2003;Bonicalzi et al, 2003). DNA-damage-induced poly(ADP-ribose) is detected within minutes, peaks by 30 minutes and returns to basal levels 15-60 minutes later (Singh et al, 1985;Tartier et al, 2003). Similar kinetics of synthesis/degradation are also observed during transcription of the hsp70 locus in Drosophila (Tulin and Spradling, 2003).…”
Section: Poly(adp-ribose) Glycohydrolase and Chromatin Recondensationmentioning
confidence: 76%
“…Since in this case the mechanism of activation of poly(ADP-ribose) synthase is possibly divergent from that assumed for the alkylation-mediated stimulation of poly(ADP-ribose) synthesis [64], it is noteworthy that very similar proteins were found to serve as major acceptors. Furthermore, recent studies applying a new technique to label endogenous poly(ADP-ribose) -protein conjugates specifically in growing human colon adenocarcinoma cells 1651 revealed that the label was preferentially incorporated into peptides with electrophoretic mobilities similar to histones and to poly(ADP-ribose) synthase, suggesting that modification of these acceptors might be of more general significance.…”
Section: Discussionmentioning
confidence: 86%
“…DMBA has been shown to bind to DNA and cause mutations particularly in the H-ras gene, which is normally involved with proliferation and differentiation (36). The tumor promoter TPA triggers ROS production and causes hyperplasia in skin cells with H-ras mutations, which leads ultimately to the formation of papillomas (36,37). CR is protective against the promotion phase of the two-stage carcinogenesis model and decreases tumor incidence and multiplicity (38).…”
mentioning
confidence: 99%